Model Bimbingan Kelompok Dengan Teknik Diskusi Untuk Meningkatkan Konsentrasi Belajar Siswa Fase F - Yulianti, Dina; Triyono, Triyono; Chandra, Yasrial (Jurnal Bimbingan dan Konseling Pandohop, 2025)
This research is based on the background of students who are still unable to concentrate in the face of pressure during lessons. Their attention is increasingly divided by various things, so that learning is increasingly unconducive and undirected. The purpose of this study is to 1) describe students' learning concentration. 2) Test the design model of group guidance services with discussion techniques to improve students' learning concentration. This research was conducted using the research and development method. The population in this study was 252 people. The sample in this study used propotional random sampling technique with a sample size of 72 people. The development procedure used in this study includes 5 steps, namely: 1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design revision, resulting in the final product design of the responsive service model in the field of social development. The data collection technique used is a questionnaire using a percentage data analysis technique. Based on the results of the research about can be seen from: 1) The description of student learning concentration is in the good category. 2) The group guidance service design model with discussion techniques to improve student learning concentration that has been validated by theoretical experts is categorized as “acceptable” and feasible to use. Based on the results of this study, it is recommended that guidance and counseling teachers use the model to improve students' learning concentration.